Development of Interactive Learning Media Based on Differentiated Learning Styles to Improve Literacy and Numeracy in Early Childhood - Widianingsih, Komang Tri; Jampel, I Nyoman; Astawan, I Gede (Universitas Pendidikan Mandalika, 2025)
This study aims to develop, validate, and evaluate the practicality and effectiveness of differentiated interactive learning media based on learning styles to improve early literacy and numeracy. The research applied an R&D method following the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The participants were 30 children aged 5–6 years, divided into experimental and control groups. Instruments included literacy and numeracy tests, expert validation sheets, and practicality questionnaires for teachers and children. Data were analyzed using normality and homogeneity tests and MANOVA with SPSS 26. The findings showed that the media was highly valid (Aiken’s V > 0.90), very practical (teacher response 95.56% and children’s response 91.48%), and effective in improving literacy (F = 20.711; p < 0.001; R² = 0.425) and numeracy (F = 63.439; p < 0.001; R² = 0.694). The more substantial effect on numeracy reflected the role of concrete and kinesthetic activities, while audio-visual features supported literacy gains. These results confirm that the differentiated interactive learning media is a pedagogically relevant tool to support literacy and numeracy achievement within the Merdeka Curriculum.